Rancang Bangun Alat Ukur Emisi Gas Buang Kendaraan Bermotor Dengan Penampil Smartphone Android - Refi Widya; Melly Syahfitri; Taufiq Hidayat; Khalil Afif; Sinekmehuli Br Perangin Angin (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
Air pollution has become an increasingly complex and worrying global problem, with motor vehicles playing a key role as the main contributor Every year, millions of vehicles operate on the road, producing an ever-increasing volume of exhaust gas and having a continuing negative impact on air quality and public health. The composition of motor vehicle exhaust gas is very complex and contains a number of hazardous compounds Carbon monoxide, nitrogen oxides, hydrocarbons, sulfur dioxide, and dust particles are some of the main components produced from the fuel combustion process These compounds not only pollute the air but also directly affect human health. Conventional measurement methods generally require expensive equipment, complicated procedures, and can only be accessed by certain institutions or agencies. As a result, the general public has practically no direct access to find out the emission conditions of the vehicles they use every day. This limitation creates a significant information gap between technical data and public awareness. Modern smartphones are no longer just communication tools, but have evolved into sophisticated computing devices. Therefore, the author utilizes smartphones with the aim of displaying the accuracy, reliability, and reproducibility of measurement results produced by the system. The significance of the research is not only limited to the technological aspect, but also has strategic implications in environmental management. By providing democratic access to emission information, this research has the potential to empower communities to actively participate in air pollution control efforts. Moreover, this research is a strategic effort to transform the way communities understand, measure, and respond to environmental challenges in the digital era. From the results of the MQ-7 gas sensor test, it works at a minimum range of 300-500ppm at Hazardous air status. To reach the minimum measurement point of the MQ-2 and MQ-7 gas sensors requires quite a long time.